Bioprospecting of a Novel Plant Growth-Promoting Bacterium Bacillus Altitudinis KP-14 for Enhancing Miscanthus × giganteus Growth in Metals Contaminated Soil - Pranaw, Kumar; Pidlisnyuk, Valentina; Trögl, Josef; Malinská, Hana (Biology, 2020)
Use of plant growth-promoting bacteria (PGPB) for cultivation of the biofuel crop Miscanthus × giganteus (Mxg) in post-military and post-mining sites is a promising approach for the bioremediation of soils contaminated by metals. In the present study, PGPB were isolated from contaminated soil and screened for tolerance against abiotic stresses caused by salinity, pH, temperature, and lead (Pb). Selected strains were further assessed and screened for plant growth-promoting attributes. The isolate showing the most potential, Bacillus altitudinis KP-14, was tested for enhancement of Mxg growth in contaminated soil under greenhouse conditions. It was found to be highly tolerant to diverse abiotic stresses, exhibiting tolerance to salinity (0-15%), pH (4-8), temperature (4-50 °C), and Pb (up to 1200 ppm). The association of B. altitudinis KP-14 with Mxg resulted in a significant (p ≤ 0.001) impact on biomass enhancement: the total shoot and dry root weights were significantly enhanced by 77.7% and 55.5%, respectively. The significant enhancement of Mxg biomass parameters by application of B. altitudinis KP-14 strongly supports the use of this strain as a biofertilizer for the improvement of plant growth in metal-contaminated soils.
Keywords: Miscanthus × giganteus; abiotic stress; lead tolerance; P-solubilization; Bacillus altitudinis; post-mining metal-contaminated soil